2008
DOI: 10.1007/s10549-008-9988-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of anti-apoptotic proteins in non-involved tissue from cancer-containing breasts

Abstract: In a previous investigation reduced apoptosis was identified in normal breast tissue from cancer-containing breasts away from the cancer in comparison to age-matched normal breast from women without cancer. The hypothesis for this study was that defects in expression of apoptotic regulatory and DNA repair proteins would facilitate persistence of genetic alterations and predispose to breast cancer development.Using immunohistochemistry normal breast from 120 age-matched women (58 with breast cancer, 62 without)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…38,39]. Normal breast tissue from healthy women shows lower expression of Bcl-2 protein than normal breast tissue in women with cancer and in cancer tissue [40]. In breast carcinoma, Bcl-2 has been described as an independent prognostic and predictive marker [41,42,43] and loss of its expression in high risk breast carcinoma has been related to increased overall mortality, distinct metastasis and locoregional recurrence [44].…”
Section: Discussionmentioning
confidence: 99%
“…38,39]. Normal breast tissue from healthy women shows lower expression of Bcl-2 protein than normal breast tissue in women with cancer and in cancer tissue [40]. In breast carcinoma, Bcl-2 has been described as an independent prognostic and predictive marker [41,42,43] and loss of its expression in high risk breast carcinoma has been related to increased overall mortality, distinct metastasis and locoregional recurrence [44].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB1 regulates apoptosis through its interaction with Pro-CASP3 (Rocchi et al 2006;Batchelder et al 2009), AKT1 (Rane et al 2003), and CYC1 (Pandey et al 2000). According to Rane et al (2003), disruption of the interaction between HSPB1 and AKT1 impairs AKT1 activation, leading to an enhanced rate of apoptosis.…”
Section: Rp101-mediated Inhibition Of Hspb1 Interactionsmentioning
confidence: 99%
“…It regulates apoptosis through interaction with STAT3 (Song et al 2004;Hsieh et al 2005;Rocchi et al 2005;Lee et al 2008), CYC1 (Cytochrome c-1) (Pandey et al 2000), and CASP3 (Caspase 3) (Rocchi et al 2006;Batchelder et al 2009). It has been suggested that the anti-apoptotic eVect of HSPB1 overexpression is associated with altered DNA topoisomerase II expression (Hansen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular expression of Hsp27 modulates the ability of cells to respond to several types of injury, including heat shock, oxidative stress and chemical stress in order to offset the deleterious effects of cellular stresses [10,11]. Hsp27 has also been identified as an antiapoptotic factor which confers a survival advantage to cells by reduction of apoptosis [12,13]. Diagnostic test study has indicated Hsp27 is a sensitive biomarker for detection of early AKI in critically ill patients [14].…”
Section: Introductionmentioning
confidence: 99%